THE IMPACT OF GLOBALIZATION ON THE ECONOMY OF THE REPUBLIC OF CROATIA (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2019)
Globalization and globalization processes that have been particularly noticeable in the last few decades have made an impact on the transfer of power centres and have significantly changed the geopolitical picture of the world. In order to affect globalization, its impact must be measured, but the first precondition is to understand globalization in order to be able to properly measure it at all. Measuring a complex phenomenon such as globalization requires the inclusion of a number of elements on which measuring will be based, such as measuring the social, economic, political and ecological dimensions of globalization. Certain elements of globalization are harder to measure because the indicators involved in each element are not entirely appropriate. Economic globalization is mostly made up of economic indicators that are unequivocal and comparable, while social or political globalization is determined by indicators that depend on economic strength and state development. Globalization processes have significantly influenced the economy of the Republic of Croatia as well as the state of the environment. The aim of the paper is to provide a comprehensive overview of the globalization trends within the Croatian economy as well as a comparison between the Croatian economy and the economies of neighbouring countries that have had a similar transition path based on the composite globalization index. In this paper, a regression analysis of individual elements within the composite globalization index was conducted.